A case of White–Sutton syndrome arising from a maternally-inherited mutation in POGZ. (August 2021) - Liu, Siqin; Yan, Zhenxing; Huang, Yaowei; Zheng, Wenxia; Deng, Yiting; Zou, Yang; Xie, Huifang
Abstract : POGZ is located on chromosome 1q21.3, encoding a pogo transposable element-derived protein with a zinc finger cluster. White–Sutton syndrome (WHSUS, OMIM:616364) is a genetic disorder resulting from de novo heterozygous pathogenic variants in POGZ, which manifests as intellectual disability, autism spectrum disorder, specific facial features and other phenotypic spectra. To date, a total of twenty-one de novo POGZ mutations in WHSUS have been reported. Here we report the identification of a novel missense variant in the coding region of the POGZ gene (c.4042G>C), which occurred in a 15-year-old male and his mother with WHSUS. We describe their clinical features and compare them with clinical data of patients with WHSUS from the literature. Our finding broadens the spectrum of POGZ mutations and provides a good example of precision medicine through the combination of exome sequencing and clinical testing.